Implication of Medical Treatment for Surgical Strategies in IBD - Gecse, Krisztina B.; Buskens, Christianne J. (Current Drug Targets, 2019)
Despite changing medical paradigm, still a significant proportion of patients with IBD require surgery. The patient's general condition, including nutritional status and the use of immunosuppressive medications is of great importance with regard to surgical complications, as well as the choice of optimal surgical strategy. The indication and the timing of surgery are key factors for the multidisciplinary management of IBD patients. The purpose of this review is to provide an overview on the impact of medical treatment on surgical strategies in IBD.
Keywords: ulcerative colitis